2019
DOI: 10.3758/s13414-019-01835-z
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modal correspondences in sine wave: Speech versus non-speech modes

Abstract: The present study aimed to investigate whether or not the so-called "bouba-kiki" effect is mediated by speech-specific representations. Sine-wave versions of naturally produced pseudowords were used as auditory stimuli in an implicit association task (IAT) and an explicit cross-modal matching (CMM) task to examine cross-modal shape-sound correspondences. A group of participants trained to hear the sine-wave stimuli as speech was compared to a group that heard them as non-speech sounds. Sound-shape corresponden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Particularly telling in this context is a study by Silva and Bellini-Leite (2019), who demonstrate that we observe similar sound symbolic effects when listeners are presented with sine-wave analogues of taketeand maluma-like speech. For such non-speech analogues, there are no articulatory actions that listeners can recover from the stimuli.…”
Section: Articulatory Explanationmentioning
confidence: 71%
“…Particularly telling in this context is a study by Silva and Bellini-Leite (2019), who demonstrate that we observe similar sound symbolic effects when listeners are presented with sine-wave analogues of taketeand maluma-like speech. For such non-speech analogues, there are no articulatory actions that listeners can recover from the stimuli.…”
Section: Articulatory Explanationmentioning
confidence: 71%
“… Sidhu and Pexman (2018) have provided a comprehensive review of potential sound symbolism mechanisms proposing that there is such wide variability of sound symbolism phenomena that many different sound symbolism effects can be based on different mechanisms, and correspondingly a specific sound symbolism effect can be based on more than one mechanism. As an example, although lip rounding might map rounded vowels with round-edged shapes in the bouba-kiki effect , it has been also shown that participants associate sine-wave versions of the pseudowords maluma and taketa with round and sharp-edged shapes, respectively ( Silva and Bellini-Leite, 2020 ), suggesting that purely acoustic properties of these words can provide characteristics that enable linking them to particular shapes. Similarly, the acoustic and articulatory accounts of the sound-magnitude effect are not mutually exclusive, and it is possible that both of them are valid.…”
Section: Sound-action Symbolismmentioning
confidence: 99%
“…Stemming largely from its theoretical importance to questions of language evolution, the bouba/kiki effect has been replicated and extended numerous times in wide-ranging experiments, serving as a testbed for understanding the psychology of crossmodal correspondence in communication [48][49][50][51][52][53][54][55]. Moreover, while experiments using pseudowords have often been criticized for having limited relevance to spoken language vocabularies [56][57][58], recent evidence shows that the effect may actually influence the vocabularies of modern languages.…”
Section: Introductionmentioning
confidence: 99%